2021
DOI: 10.1177/1745691621990379
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Frequency of Inner-Experience Characteristics

Abstract: Inner experience is widely accepted by psychologists and lay people as being straightforwardly observable: Inner speech, visual images, feelings, and so on are understood to be directly apprehendable “before the footlights of consciousness.” Many psychologists hold that such characteristics of inner experience play substantial theoretical roles and have applied significance across a wide range of cognitive, affective, performance, and clinical situations. If so, the frequency of occurrence of these characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 39 publications
1
25
1
Order By: Relevance
“…Reports are more likely to be accurate if participants are asked to simply report their experiences without attempting to theorise about the causes of their behaviour (Berger et al, 2016;Johansson et al, 2005;Petitmengin et al, 2013). This is in line with previous findings that questionnaire measures of inner speech have low correlation with more direct measures like experience sampling (Alderson-Day & Fernyhough, 2015a;Hurlburt et al, 2022).…”
Section: Limitations and Future Directionssupporting
confidence: 86%
“…Reports are more likely to be accurate if participants are asked to simply report their experiences without attempting to theorise about the causes of their behaviour (Berger et al, 2016;Johansson et al, 2005;Petitmengin et al, 2013). This is in line with previous findings that questionnaire measures of inner speech have low correlation with more direct measures like experience sampling (Alderson-Day & Fernyhough, 2015a;Hurlburt et al, 2022).…”
Section: Limitations and Future Directionssupporting
confidence: 86%
“…Only one study, to our knowledge, had ever used descriptive experience sampling in aphasia (to study flow states; Sather et al, 2017). While the best practice for dynamic sampling of inner speech appears to be mixed methodology involving descriptive experience sampling (Hurlburt et al, 2021), thought listing and interviews (Racy et al, 2020), andsurveys (Alderson-Day et al, 2018;Racy et al, 2020Racy et al, , 2022, we were not sure if this was feasible before undertaking this project. The low number of total dropouts and the high session completion is encouraging.…”
Section: Discussionmentioning
confidence: 99%
“…No matter its name, this type of assessment is defined by three critical features: people are assessed in their natural environments; researchers attempt to measure events or experiences in real-time; and researchers intensively assess people over time, such as several assessments per day across a week (Hektner et al, 2007). DES is appealing to measure inner speech because inner speech is known to vary by context and thought to not be present all of the time (Hurlburt et al, 2021). Therefore, using intensive, longitudinal methods in a real environment may most sensitively and accurately reflect experiences of inner speech.…”
Section: Descriptive Experience Sampling (Des)mentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, it was found that experience sampling-based MW reports not only reflect MW traits, but also individual tendencies to mind wander during specific tasks ( Rummel et al, 2021 ). Moreover, questionnaire-based MW data most likely to a larger extent depend on self-reflection and insight than experience sampling-based reports do ( Hurlburt et al, 2022 ). Thus, one may expect that questionnaire-based MW scores and MW propensities measured during the SART do not perfectly map onto one another.…”
Section: Discussionmentioning
confidence: 99%